Canine Staphylococcaceae circulating in a Kenyan animal shelter - Akarsu, H.; Liljander, Anne M.; Lacasta, Anna; Ssajjakambwe, P.; Brodard, I.; Cherbuin, J.D.R.; Torres-Puig, S.; Perreten, V.; Kuhnert, P.; Labroussaa, F.; Jores, Joerg (American Society for Microbiology, 2024)
Animal shelters, especially in resource-poor countries, bring together pets from different regions and with different backgrounds. The crowding of such animals often results in infectious diseases, such as respiratory infections. This study characterized Staphylococcaceae from diseased and apparently healthy dogs housed in an animal shelter in Kenya, to determine their antibiotic resistance profiles, their genetic relatedness, and the presence of dominant clones. Therefore, bacteria were collected from all 167 dogs present in the shelter in June 2015 and screened for Staphylococcaceae using standard cultivation techniques. In all, 92 strains were isolated from 85 dogs and subsequently sequenced by PacBio long-read sequencing. Strains encompassed nine validated species, while S. aureus (n = 47), S. pseudintermedius (n = 21), and Mammaliicoccus (M.) sciuri (n = 16) were the three most dominant species. Two S. aureus clones of ST15 (CC15) and ST1292 (CC1) were isolated from 7 and 37 dogs, respectively. All 92 strains isolated were tested for their antimicrobial susceptibility by determining the minimum inhibitory concentrations. In all, 86 strains had resistance-associated minimal inhibitory concentrations to at least one of the following antimicrobials: tetracycline, benzylpenicillin, oxacillin, erythromycin, clindamycin, trimethoprim, kanamycin/gentamicin, or streptomycin. Many virulence-encoding genes were detected in the S. aureus strains, other Staphylococcaceae contained a different set of homologs of such genes. The presence of mobile genetic elements, such as plasmids and prophages, known to facilitate the dissemination of virulence- and resistance-encoding genes, was also assessed. The unsuspected high presence of two S. aureus clones in about 50% of dogs suggests dissemination within the shelter and a human source.